Tailoring migration policies to address labour shortages - Katrin Sommerfeld (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Labour markets in the European Union are increasingly facing labour shortages. This ZEW Policy Brief argues that immigration from third countries should be increased to alleviate bottlenecks in the supply of workers to the economy. On the one hand, immigration policies should target high-skilled individuals and those trained in shortage occupations and allow them to search for a job from within the EU. On the other hand, low-skilled employees also appear to contribute to mitigating labour shortages. This is because labour shortages are also present in some low-skill occupations, and because additional immigrant workers could "free up" native workers to work in shortage occupations or push natives into better jobs. Therefore, this ZEW policy brief recommends enabling the immigration of such individuals when they have a job offer available. Broader policy measures should be put into place to facilitate the recognition of foreign qualifications.
Keywords: 330; Migrationspolitik; Fachkräfte; EU-Staaten